2020
DOI: 10.1038/s41467-020-18514-5
|View full text |Cite
|
Sign up to set email alerts
|

The shared frameshift mutation landscape of microsatellite-unstable cancers suggests immunoediting during tumor evolution

Abstract: The immune system can recognize and attack cancer cells, especially those with a high load of mutation-induced neoantigens. Such neoantigens are abundant in DNA mismatch repair (MMR)-deficient, microsatellite-unstable (MSI) cancers. MMR deficiency leads to insertion/deletion (indel) mutations at coding microsatellites (cMS) and to neoantigen-inducing translational frameshifts. Here, we develop a tool to quantify frameshift mutations in MSI colorectal and endometrial cancer. Our results show that frameshift mut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 92 publications
(91 citation statements)
references
References 82 publications
2
89
0
Order By: Relevance
“…Another therapeutic approach for MMR-deficient, hypermutant tumors in general is the use of immune checkpoint inhibitors to activate the immune system as they present with an increased number of neoantigens that could be detected by host immune cells [3,16,30,33,38]. Indeed, case reports of successful treatments of malignant IDH-wt brain tumors in CMMRD with checkpoint inhibitors lead to current clinical studies evaluating the potential benefit of this strategy [6,28].…”
Section: Discussionmentioning
confidence: 99%
“…Another therapeutic approach for MMR-deficient, hypermutant tumors in general is the use of immune checkpoint inhibitors to activate the immune system as they present with an increased number of neoantigens that could be detected by host immune cells [3,16,30,33,38]. Indeed, case reports of successful treatments of malignant IDH-wt brain tumors in CMMRD with checkpoint inhibitors lead to current clinical studies evaluating the potential benefit of this strategy [6,28].…”
Section: Discussionmentioning
confidence: 99%
“…Variant calling of InDel mutations remains challenging to date (44) and although the usage of public mutation databases is accepted as a reasonable substitute for sequencing (18), it must be considered that the data used for the construction of our InDel neoepitope databases might be incomplete or biased. Indeed, the length of mutated microsatellites resulting in identified InDel neoepitopes was rather short (4 -8 bp) and we did not document InDel neoepitopes derived from well-established InDel mutations occurring in longer repetitive sequences of the HCT-116 cell line as the mutations are not documented in either the COSMIC or CCLE database.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the length of mutated microsatellites resulting in identified InDel neoepitopes was rather short (4 -8 bp) and we did not document InDel neoepitopes derived from well-established InDel mutations occurring in longer repetitive sequences of the HCT-116 cell line as the mutations are not documented in either the COSMIC or CCLE database. To address this limitation we also searched our MS raw data against a database of frequent InDel mutations in MSI CRC (44), although this did not yield new InDel neoepitope identifications. In future studies, this limitation may be overcome and more InDel neoepitopes might be identified by utilizing long-read sequencing technologies (45).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations